Investigation of fabrication techniques, characteristics and applications of microfiber devices / Lim Kok Sing - Lim, Kok Sing (2012)
Microfiber devices have great potential in numerous applications as they offer a number of unique characteristics and optical properties. In this thesis, the background theory and fabrication techniques of microfiber devices are introduced. A high precision computer-controlled rig based on flame brushing technique was assembled in the laboratory.